Comunicação ambiental e educação ambiental em bacias hidrográficas: concepções, abordagens, práticas e indicadores para avaliação - Dictoro, Vinicius Perez (2021)
The present study had as its guiding themes environmental education, environmental communication, watershed management and the use of evaluation indicators. Themes that were thought based on a systemic and integrated vision of human beings with the environment and with the other living beings on the planet. The main objective of this study was to investigate concepts, practices and approaches to environmental communication and environmental education in river basins, aiming to establish specific instruments, criteria and indicators for the analysis of projects and activities in watersheds. To support the reflections made in the study, a systemic and complex approach was adopted. In order to achieve the proposed objectives, bibliographic research techniques (systematic bibliographic review), exploratory and applied research (questionnaires with members of river basin committees and experts from related areas) were used, which allowed the collection of data and information, analyzed through bibliometric analysis techniques and the 3S validation methodology. How the main results of this thesis were generated: an instrument for evaluating proposals for environmental education projects within the scope of river basin committees; a list of indicators for evaluating environmental education actions and activities in watershed; a framework of action guidelines for environmental education activities. It is concluded that there should be a greater integration between the themes of environmental communication and environmental education, in order to increase the scope of actions and activities that can be carried out in watersheds, mobilizing and involving society, generating behaviors beneficial to the environment , in addition to understanding the current socio-environmental problems present in society and contributing to the creation of a new paradigm of the relationship between human beings and the environment.